Synergistic effect of chitosan and Pseudomonas sp on the biological control of Tomato leaf curl virus in tomato - Mishra, Shefali; Jagadeesh, K S; Krishnaraj, P U; Byadagi, A S; Vastrad, A S (Indian Journal of Plant Protection, 2020)
Combined treatment of chitosan and Pseudomonas spp.induced a significant increase in the activities of polyphenoloxidase (PPO), peroxidase (POD), chitinase, phenylammonia lyase (PALase) and enhanced the content of phenolic compounds in tomato plants. Application of Pseudomonas spp.in combination with chitosan reduced the severity of Tomato leaf curl virus (ToLCV) diseased plants by 75-100% at 45 days after inoculation (DAI) relative to ToLCV control. Application of chitosan or the bacterial inoculant alone was not very effective. The plants inoculated with a mixture of Pseudomonas spp.(206(4) +B-15+ JK-16) + Chitosan recorded the highest phenol content, peroxidase activity, polyphenol oxidase activity, chitinase activity and PALase activity (65.78 %, 110.59 % ,95.65,69.26 and 71.76 % higher than the diseased control, respectively). This treatment also recorded maximum plant height, biomass and chlorophyll content, which were increased by 86.42, 41.27 and 91.50 per cent, respectively over the diseased control. This combination proved highly effective in reducing the whitefly population as well as ToLCV disease severity. The quantification of viral load was done by semi quantitative PCR analysis, which revealed the lowest viral load accumulation in plants inoculated with rhizobacterial mixture + chitosan. ToLCV particles in affected leaves were detected by electron microscopic examination of the partially purified preparation of leaf samples. Thus the study has indicated that the application of rhizobacterial mixture + chitosan effectively reduced the disease severity of ToLCV and vector population through ISR as evidenced by lower viral titre and higher production of defense molecules.